Effect of Albendazole on Tau and Stathmin Expression in Metastatic Breast Cancer - Sepideh Javdan; Ziba Rezvani Sichani; Adel Rezvani Sichani; Hashem Nayeri (Disease and Diagnosis, 2024)
Background: Cancer metastasis is the leading cause of death among cancer patients, but there are numerous treatment options available, including drugs such as albendazole (ABZ) and complementary therapies such as cannabis-based medicines, making them important targets for therapeutic interventions. The present study aimed to assess the impact of ABZ on the protein expression of Tau and Stathmin, as well as cell migration, in patients with metastatic breast cancer (BC), where these proteins play critical roles. Materials and Methods: MCF-7 and MDA-MB-231 cell lines were split into a treatment group that received varying concentrations of a standardized extract of ABZ for 48 hours and a control group that received no treatment in this study. The relative gene expression was measured using a quantitative reverse transcription-real-time polymerase chain reaction assay and the ΔΔct method. A migration assay was also performed to assess cancer metastasis. Results: Tau and Stathmin gene expression and cell migration were significantly decreased compared to the control group. Conclusion: The results of the study demonstrated that ABZ reduced both Tau and Stathmin gene expression, as well as cancer metastasis. Nonetheless, evidence suggests that we can use ABZ as an anti-tumor drug for BC treatment.